Mycoplasma contamination revisited: mesenchymal stromal cells harboring Mycoplasma hyorhinis potently inhibit lymphocyte proliferation in vitro. - Severin Zinöcker; Meng-Yu Wang; Peter Gaustad; Gunnar Kvalheim; Bent Rolstad; John T Vaage (PLoS ONE, 2011)
BACKGROUND: Mesenchymal stromal cells (MSC) have important immunomodulatory effects that can be exploited in the clinical setting, e.g. in patients suffering from graft-versus-host disease after allogeneic stem cell transplantation. In an experimental animal model, cultures of rat T lymphocytes were stimulated in vitro either with the mitogen Concanavalin A or with irradiated allogeneic cells in mixed lymphocyte reactions, the latter to simulate allo-immunogenic activation of transplanted T cells in vivo. This study investigated the inhibitory effects of rat bone marrow-derived MSC subsequently found to be infected with a common mycoplasma species (Mycoplasma hyorhinis) on T cell activation in vitro and experimental graft-versus-host disease in vivo. PRINCIPAL FINDINGS: We found that M. hyorhinis infection increased the anti-proliferative effect of MSC dramatically, as measured by both radiometric and fluorimetric methods. Inhibition could not be explained solely by the well-known ability of mycoplasmas to degrade tritiated thymidine, but likely was the result of rapid dissemination of M. hyorhinis in the lymphocyte culture. CONCLUSIONS: This study demonstrates the potent inhibitory effect exerted by M. hyorhinis in standard lymphocyte proliferation assays in vitro. MSC are efficient vectors of mycoplasma infection, emphasizing the importance of monitoring cell cultures for contamination.